2020
DOI: 10.1166/mex.2020.1752
|View full text |Cite
|
Sign up to set email alerts
|

Nacre crystal growth as a paradigm of island growth mode: Hydrophobic substrate is one of the keys to the biomineralization

Abstract: Nacre is a multilayered film material consisting of alternating layers of aragonitic tablets and organic membranes (OMs). However, at this time, no authors have discussed the growth mode of nacre from the perspective of the science of typical film materials. Here, for the first time, we focus on measuring the contact angles of the nacre growth surface (GS) using the contact angle meter. Additionally, we also investigate the GS's structure and phases using field emission scanning electron microscopy and X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Under the conditions used in our simulation the organic component remains in an amorphous or nanocrystalline state. Remarkably, the predicted “nacre” structure recovers such details of the experimentally observed microstructure as the “mineral bridges” and the line defects across the organic layers termed “aligned holes”. ,,, We will show, however, in the next section that despite this close similarity, the formation mechanism of the nacre can be considerably more complex than predicted here.…”
Section: Results and Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Under the conditions used in our simulation the organic component remains in an amorphous or nanocrystalline state. Remarkably, the predicted “nacre” structure recovers such details of the experimentally observed microstructure as the “mineral bridges” and the line defects across the organic layers termed “aligned holes”. ,,, We will show, however, in the next section that despite this close similarity, the formation mechanism of the nacre can be considerably more complex than predicted here.…”
Section: Results and Discussionsupporting
confidence: 64%
“…Finally, we note that the thickness of the organic and mineral layers in the nacre are typically 10–40 nm and 300–600 nm, 136 − 140 respectively. Our qualitative simulations give a considerably larger relative thickness for the organic layer.…”
Section: Results and Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Ikeda et al reported the difference in the in-plane crystal orientation on the glass substrate with different wettabilities in the graphoepitaxy of α-sexithiophene . Wang et al showed that hydrophobic substrate is one of the key factors to affect the Nacre crystal growth system. , As mentioned above, it is likely that the surface wettability has some influence on the produced crystal morphology. Thus, it is required to figure out the crystal growth mechanism for each substrate surface with different wettabilities through an investigation of the process where the crystal morphologies are formed.…”
Section: Introductionmentioning
confidence: 99%